Applying hofstede's cultural dimensions to manager working culture: case study of Selia Selenggara Selatan Sdn Bhd (SSSSB) / Mawar Hartini Md Mazlan - Md Mazlan, Mawar Hartini (Faculty of Business and Management, 2010)
This case study examines the applying of Hofstede Cultural Dimension to the working culture of Selia Selenggara Selatan Sdn. Bhd.(SSSSB) managers. The objective is to investigate the working culture of SSSSB managers and to identify the different and similarities between Hofstede Culture Dimension index in Malaysia to the SSSSB managers working culture. It is important to give briefly understanding the applying of theory to a working culture of Malaysian manager. However, this study only used four dimension of Hofstede culture regardless the Long-Term Orientation. The study uses personal interviewing as the primary data collection method. The researcher conducted in-depth interviews with two managers of SSSSB managers who have wide experience to work in domestic and international market as behalf of SSSSB. Variety types of Internal and external sources also used as secondary data. The findings disclose that the SSSSB manager’s working culture has similarities in Power Distance and Collectivism with Hofstede Cultural Dimension index. However, they have different result in Masculinity and Femininity, also in Uncertainty Avoidance. This is a significant finding that differs from what have been predicted in the published studies of Hofstede Cultural Dimension. The study explain the working culture of SSSSB managers and also shows the differences and the similarities of Hofstede Culture Dimension and actual working culture of SSSSB manager. This can bring to further study to Malaysia study of culture.